Correction: Hematopoietic stem cell transplantation for children with acute myeloid leukemia-results of the AML SCT-BFM 2007 trial - Sauer, Martin G; Lang, Peter J; Albert, Michael H; Bader, Peter; Creutzig, Ursula; Eyrich, Matthias; Greil, Johann; Gruhn, Bernd; Holter, Wolfgang; Klingebiel, Thomas; Kremens, Bernhard; von der Leyen, Heiko; et al. (Leukemia, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.